'It's like a never‐ending diabetes youth camp': Co‐designing a digital social network for young people with type 1 diabetes - Kerstin Ramfelt; Boel Andersson Gäre; Ann‐Christine Andersson; Christina Petersson (Wiley, 2023)
Abstract Introduction Living with a chronic condition such as type 1 diabetes (T1D) affects everyday life and support from others experiencing a similar situation can be helpful. A way to receive such support is to use an online network where people can connect and share experiences. Research has described the benefits of using such tools for connecting patients. The aim of this study was to describe the co‐design of a social network for young people with T1D and to describe their experiences when using this network. Methods A co‐design approach was used, following three steps adapted from Sanders and Stappers (2008). In all, 36 adolescents with T1D participated. Data in the form of recordings and notes from telephone interviews, workshops and focus groups were collected and then analysed using content analysis. Numerical data from the digital platform were also used. Findings For the interpersonal values, supporting, learning and relating to emerge, the framework of the network must be appealing and user‐friendly. The limits of time and place are eliminated, and there is a possibility for many more to join in. Conclusion Co‐design ensures that what stakeholders think is important forms the basis for the design. The interpersonal values that are promoted are ones that only the exchange of lived knowledge and experience can generate. It is complementary to the support that healthcare professionals can offer; thus, this kind of social network is important for improved, coproduced care. Patient or Public Contribution The participants in the present study were persons living with T1D. They were active co‐creators from the start to the end. An adult person with experience of living with T1D was involved as an advisor in the research team when drafting the manuscript.